Kinematics and kinetics of maximum running speed in youth across maturity - Rumpf, M. C.; Cronin, J. B.; Oliver, J.; Hughes, M. (Pediatric Exercise Science, 2015)
Sprinting is an important physical capacity and the development of sprint ability can take place throughout the athlete`s growth. The purpose of this study therefore was to determine if the kinematics and kinetics associated with maximum sprint velocity differs in male youth participants of different maturity status (pre, mid- and postpeak height velocity (PHV)) and if maximum sprint velocity is determined by age, maturity or individual body size measurement. Participants (n = 74) sprinted over 30 meters on a nonmotorized treadmill and the fastest four consecutive steps were analyzed. Pre-PHV participants were found to differ significantly (p < .05) to mid- and post-PHV participants in speed, step length, step frequency, vertical and horizontal force, and horizontal power (~8-78%). However, only relative vertical force and speed differed significantly between mid and post-PHV groups. The greatest average percent change in kinetics and kinematics was observed from pre- to mid-PHV (37.8%) compared with mid- to post- PHV groups (11.6%). When maturity offset was entered as a covariate, there was no significant difference in velocity between the three groups. However, all groups were significantly different from each other when age was chosen as the covariate. The two best predictors of maximal velocity within each maturity group were power and horizontal force (R2 = 97-99%) indicating the importance of horizontal force application while sprinting. Finally, maturity explained 83% of maximal velocity across all groups.